PROFIL TINGKAT KEPUASAN PASIEN RAWAT JALAN UMUM TERHADAP PELAYANAN KEFARMASIAN DI RSUD KEFAMENANUBULAN JULI TAHUN 2011 - NI NYOMAN YULIANI; JEFRIN SAMBARA; MARIA HILARIA; MARIA ELISABETH MANIKIN (JURNAL INFO KESEHATAN, 2013)
Satisfaction is a goal that is often applied/designed to measure the gap between the quality of service they received with the expected quality of service. Level ofpatient satisfactionwas measured by five dimensions ofquality of the service, namely reliability(Reability), Responsiveness (responsivenes), empathy(Emphaty), confidence(Assurance), andappearance(Tangible). This study was conducted to determine the level of patient satisfaction with the level of reliability, level of responsiveness, level of confidence, the level of empathy, and the rate of appearance of pharmaceutical services at the District General Hospital Kefamenanu. The research was done by filling the question naire by the patientis then calculated presentation of the patient'slevel of satisfaction indicators studied. Based on the calculation of the level of patient satisfaction indicators at responsiveness of 40.75% gave values some what satisfied, 44.5% reliability give satisfied, 45.25% confidence give satisfaction, delivering value empathy39.05% satisfied, 41% give the appearance of satisfied.